Impact of bandwidth-constrained media-specific forward error correction schemes on voice over IP - Lee, Kah Wah. (2008)
In line with the proposed solution techniques, the research methodology in this thesis centers on loss data accumulation via Internet measurements, network loss modeling and analytical results.In this thesis, the performance of the proposed solution techniques of bandwidth-constrained media-specific FEC for VoIP is evaluated.